2022
DOI: 10.3390/molecules27072090
|View full text |Cite
|
Sign up to set email alerts
|

Pilot-Scale Optimization of Supercritical CO2 Extraction of Dry Paprika Capsicum annuum: Influence of Operational Conditions and Storage on Extract Composition

Abstract: Supercritical carbon dioxide extraction was used to extract carotenoids from dry paprika Capsicum annuum. Studies regarding the effect of process parameters, including pressure (25–45 MPa), temperature (40–60 °C), and time (10–110 min), were carried out using response surface methodology. It was found that under optimal conditions (pressure of 45 MPa, temperature of 50 °C, and time of 74 min), the extract yield was 10.05%, and the total content of carotenoids in the extract was 4.21%, in good agreement with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The negative effects of extrusion on the yield and quality of oleoresin prior to supercritical-CO 2 (SC-CO 2 ) extraction were studied, and it was concluded that irrespective of the pretreatments the maximum yield was obtained at extreme temperature and pressure conditions (60 °C and 50 MPa) and that the extractable color positively correlated with the antioxidant activity of the oleoresin extracts . Total 4.21% carotenoids were obtained from SFE at the optimum conditions of 45 MPa pressure and 50 °C temperature for 74 min form dry C. annuum powder . Although sophisticated instrumentation is required, SFE and PLE provide less oxidative atmosphere for the extracts; operate under low light, which is particularly helpful for pigments; and utilize up to 90% less solvent than other solvent extraction methods.…”
Section: Extraction Methods For Enhanced Yield Of Capsicum Oleoresinmentioning
confidence: 99%
See 1 more Smart Citation
“…The negative effects of extrusion on the yield and quality of oleoresin prior to supercritical-CO 2 (SC-CO 2 ) extraction were studied, and it was concluded that irrespective of the pretreatments the maximum yield was obtained at extreme temperature and pressure conditions (60 °C and 50 MPa) and that the extractable color positively correlated with the antioxidant activity of the oleoresin extracts . Total 4.21% carotenoids were obtained from SFE at the optimum conditions of 45 MPa pressure and 50 °C temperature for 74 min form dry C. annuum powder . Although sophisticated instrumentation is required, SFE and PLE provide less oxidative atmosphere for the extracts; operate under low light, which is particularly helpful for pigments; and utilize up to 90% less solvent than other solvent extraction methods.…”
Section: Extraction Methods For Enhanced Yield Of Capsicum Oleoresinmentioning
confidence: 99%
“…235 Total 4.21% carotenoids were obtained from SFE at the optimum conditions of 45 MPa pressure and 50 °C temperature for 74 min form dry C. annuum powder. 236 Although sophisticated instrumentation is required, SFE and PLE provide less oxidative atmosphere for the extracts; operate under low light, which is particularly helpful for pigments; and utilize up to 90% less solvent than other solvent extraction methods.…”
Section: Enzymatic Extractionmentioning
confidence: 99%
“…In addition, extraction methods influence the amounts of fatty acids. Combining solvent extraction, microwave irradiation, ultrasonic extraction and supercritical carbon dioxide techniques could significantly improve oil performance [11]. Kostrzewa et al (2022) used supercritical CO 2 extraction of dry paprika and n-hexane, and the results showed that there is no difference between the two extraction methods.…”
Section: Introductionmentioning
confidence: 99%
“…Kostrzewa et al (2022) used supercritical CO 2 extraction of dry paprika and n-hexane, and the results showed that there is no difference between the two extraction methods. [11]. Ultrasound-assisted extraction is a simple and ecologically safe method for the extraction of oil.…”
Section: Introductionmentioning
confidence: 99%